1953
DOI: 10.1021/jo01130a014
|View full text |Cite
|
Sign up to set email alerts
|

ACETYLATION AND RING CLOSURE IN REDUCTION OF NITRO- AND NITROAMINO-GUANIDINE1

Abstract: Guanidine and 1-acetamidoguanidine have been isolated from the hydrogenation of nitroguanidine in acetic acid. Large ratios of catalyst to substrate are necessary for the successful hydrogenation of nitroaminoguanidine in this media. Nitroaminoguanidine undergoes acetylation in acetic acid under mild conditions and the l-acetamido-2-nitroguanidine hydrogenates with much greater ease than the parent substance.l-Aeetamido-2-aminoguanidine can be recovered as derivatives from the reduction products if mild condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1961
1961
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…closure occurs to yield 4,5-diamino-3methyl-1,2,4-477-triazole(224,307). The formation of the triazole arises from a prior acetylation of nitroaminoguanidine which immediately undergoes ring closure on reduction.…”
mentioning
confidence: 99%
“…closure occurs to yield 4,5-diamino-3methyl-1,2,4-477-triazole(224,307). The formation of the triazole arises from a prior acetylation of nitroaminoguanidine which immediately undergoes ring closure on reduction.…”
mentioning
confidence: 99%
“…Theoretically, the cyclization reaction of compound 16 may occur at N 1 , N 2 or N 3 and lead to the formation of the corresponding three products. However, the evidence suggested that this ring-closure reaction occurred mainly at N 2 , and 3-methyl-4,5-diamino-l, 2,4-triazole ( 17) was easily obtained, as seen in Scheme 6 [45]. Reaction with oxalic acid in aqueous solution at 92–94 °C for 8 h resulted in the corresponding mono- and di-hydrazides, compounds 18 and 19 .…”
Section: Reactivity Of Anqmentioning
confidence: 99%
“…Benzylideneaminoguanidine (37) is methylated with methyl iodide, and the intermediate (38) hydrolysed to I-amino-I -methylguanidine (39) which, on treatment with benzoyl chloride, yields the cyclized product (40) as a benzoyl derivative in one step. Direct reaction of benzoyl chloride with (38) does not result in cyclization, but only gives 1 -benzylidineamino-3-benzoyl-lmethylguanidine (41).…”
Section: IImentioning
confidence: 99%
“…Reductions of nitroguanidine carried out in acetic acid produce 3-amino-5-methyl-l,2,4-triazole as a by-product [37, 421. Nitroaminoguanidine similarly affords 3,4-diamino-5-methyl-l,2,4-triazole [37, 421 as a by-product, the structure of which is confirmed by diazotization in the presence of hypophosphorous acid, when removal of both amino groups yields the known compound 3-methyl-l,2,4-triazole [37] in 63 yield. The initial diazotization product can be coupled with P-naphthol to afford the azo dye, 1-(3-methyl-1,2,4triazol-5-yl)azo-2-naphthol, which is also obtainable by diazotization and coupling of 3-amino-5-methyl-l,2,4triazole [37].…”
Section: Reduction Of Nitroguunitlines In the Presence Of Acidsmentioning
confidence: 99%